Shoulder Optimization and Motion Simulation of a 7-DOF Exoskeleton Upper Limb Rehabilitation Robot - Liu Jiajun; Zhang Xinbo; Xie Yinhui; Li Jun; Lin Guijuan; Gong Qingzhong (Jixie chuandong)
A 7-DOF exoskeleton upper-limb rehabilitation robot is designed for the needs of rehabilitation training ability enhancement of arm movement disorders. The flat motors and harmonic reducers are used as drivers, and the shoulder joint is optimized. Compared with the traditional structure, the workspace proportion of the shoulder connecting rod mechanism is reduced by 45.97%, and the structural stiffness is improved. Forward and inverse kinematics of the robot are solved and verified by the D-H parameter method. The Monte Carlo method is used to analyze the workspace of the robot to prove the rationality of the structure design. The Matlab robot toolbox is used to simulate the trajectory of the robot end. The results show that the angular displacement, angular velocity and angular acceleration of each joint change continuously and smoothly respectively during the movement of the robot, which verifies the rationality and effectiveness of the robot, and the exoskeleton upper limb robot meets the requirement of human arm rehabilitation training and exercise capacity enhancement.